Structural features of the interblock boundary in the twoslab structure of compounds of the AIILn2B2 IIIO7 (AII = Sr, Ba, Ln, BIII = Al, Fe, Sc, In) type - Titov, Y.A.; Belyavina, N.M.; Chumak, V.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
We have determined the boundaries of the existence and the structural features of the slab perovskite-like structure (SPS) of BaLa2–xSmxIn2O7 (0 ≤ х ≤ 1.8) and BaNd2–xSmxIn2O7 (0 ≤ х ≤ 1.8) systems have been established. The values of reliability factors RB are within the intervals of 0.037-0.057 for BaLa2–xSmxIn2O7 and 0.032-0.057 for BaNd2–xSmxIn2O7. The analysis of the structural features of SPS compounds and phases of the AIILn2B2IIIO7 (AII = Sr, Ba, BIII = Al, Fe, Sc, In) has revealed the interconnection between their composition and the features of the SPS interblock boundary. A decrease in the size of REE atoms in the series of compounds and phases of the AIILn2B2IIIO7 (AII = Sr, Ba) type leads to a gradual decrease in the interblock distance length (AII, Ln) — O and to a successive increase in the degree of deformation of interblock polyhedra (AII, Ln)O9. In the series of SrLn2B2IIIO7 (BIII = Al, Sc) compounds, a decrease in the size of REE atoms leads to a gradual change in the nature of the distribution of Sr and REE atoms in their SPS: from a partially ordered one (Ln = La) with the predominant localization of Sr atoms in the intrablock AO12 polyhedra to the completely ordered one (Ln = Eu, Gd, Tb, BIII = Sc) or almost completely ordered one (Ln = Ho, BIII = Al) with Sr a toms localized only in AO12 polyhedra, while smaller REE atoms are localized only in the interblock polyhedra. In the series of compounds and phases of the BaLn2B2IIIO7 type, there is a completely ordered arrangement of large Ba atoms in the intrablock AO12 polyhedra of their SPS, and the REE atoms only in the AO9 interblock polyhedra. It has been found that, in compounds the similar by the elemental composition to the An+1BnO3n+1- type, the thickness of the perovskite-like block significantly (by 2-6 times) increases the degree of deformation of the AO9 polyhedra and decreases the length of the A—O interblock bond. The analysis of the obtained data has shown that the values of the degree of deformation of the interblock polyhedra (АII, Ln)О9 and the length of the interblock bonds (АII, Ln)—О are among the main factors determining the stability of two-slab compounds of the AIILn2B2IIIO7-type.